Analisis dan Optimasi Alur Kerja Fabrikasi Sheet Metal Menggunakan FlexSim: Analisis dan Optimasi Alur Kerja Fabrikasi Sheet Metal Menggunakan FlexSim - Maulana, Yudi; Suhendi, Agus (Universitas Pamulang, 2024)
This study aims to analyze and optimize the workflow in the sheet metal fabrication production process using FlexSim simulation software. The research focuses on a manufacturing company engaged in sheet metal fabrication, covering the entire process from raw material arrival to finished products. By utilizing FlexSim, this study seeks to significantly improve production efficiency and reduce cycle time. The tools used in this research include FlexSim for workflow modeling and simulation, as well as statistical analysis software to evaluate the simulation results. The data analyzed includes process time at each workstation, waiting time between stages, production capacity, and resource utilization. Through modeling and simulation, this study successfully identifies bottlenecks and inefficiencies within the production workflow. Based on the simulation results, the implemented optimization strategies lead to a 25% increase in production efficiency and a 15% reduction in cycle time. The optimization strategies involve improving facility layout, adjusting workforce allocation, and rescheduling production to minimize waiting time and enhance workflow. Thus, this study demonstrates that using FlexSim as a simulation tool provides deeper insights into the sheet metal fabrication process and supports data-driven decision-making to improve overall production system performance. Keywords: Sheet Metal Fabrication, FlexSim, Simulation, Work Flow, Optimization, Production Efficiency